Pengaruh Literasi Keuangan dan Inklusi Keuangan Terhadap Keputusan Investasi Reksadana: Studi Kasus Pada Mahasiswa S1-Akuntansi Universitas STEKOM - Bambang Widjanarko Susilo; Benny Cuaca; Edy Susanto; Zarah Dinul Khaq; Galuh Aninditiyah; Ayu Miranti Kusumaningrum; Rezky Eko Prasetyo; Febryantahanuji Febryantahanuji (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This study analyzes the influence of financial literacy and financial inclusion on mutual fund investment decisions at issuer brokers using Partial Least Squares Structural Equation Modeling (PLS-SEM). The sample consisted of 100 S1 Management students who actively invested in mutual funds through issuer brokers. Data was collected through an online questionnaire with 24 measurement indicators that have been tested for validity and reliability. The results of the PLS-SEM analysis showed that financial literacy had a positive and significant effect on mutual fund investment decisions (β = 0.501; t = 7.724; p < 0.001). Financial inclusion also had a positive and significant effect (β = 0.414; t = 6.194; p < 0.001). The R² value for the investment decision variable is 0.608, indicating that 60.8% of the variation in investment decision can be explained by both exogenous variables. Outer loading of all indicators was above 0.70 with Average Variance Extracted (AVE) > 0.50 and Composite Reliability (CR) > 0.70, meeting the criteria of convergent validity and reliability. These findings affirm the importance of improving financial literacy and financial inclusion to encourage the quality of mutual fund investment decisions among students.